Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/ps.1661
|View full text |Cite
|
Sign up to set email alerts
|

An analogue of piperonyl butoxide facilitates the characterisation of metabolic resistance

Abstract: Using examples of resistant insects with well-characterised resistance mechanisms, a combination of PBO and analogue allows identification of the metabolic mechanism responsible for conferring resistance. The relative potency of PBO as both an esterase inhibitor and an oxidase inhibitor is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…The higher susceptibility to chlorpyrifos-ethyl in the pyrethroid resistant populations probably relates to the prevailing mechanism of resistance detected in populations from Central Europe (Philippou et al 2011). That is metabolic resistance which is based mainly on enhanced oxi- Oxidative enzymes (cytochrome P 450 monooxygenases) play the most important role in detoxification of pyrethroids in insect bodies (Moores et al 2009;Philippou et al 2011). High synergy of pyrethroid insecticides with piperonyl butoxid (the inhibitor of oxidative enzymes) and low synergy with carbaryl and tributyltin acetate (Wegorek et al 2007) confirm the above statements.…”
Section: Discussionmentioning
confidence: 99%
“…The higher susceptibility to chlorpyrifos-ethyl in the pyrethroid resistant populations probably relates to the prevailing mechanism of resistance detected in populations from Central Europe (Philippou et al 2011). That is metabolic resistance which is based mainly on enhanced oxi- Oxidative enzymes (cytochrome P 450 monooxygenases) play the most important role in detoxification of pyrethroids in insect bodies (Moores et al 2009;Philippou et al 2011). High synergy of pyrethroid insecticides with piperonyl butoxid (the inhibitor of oxidative enzymes) and low synergy with carbaryl and tributyltin acetate (Wegorek et al 2007) confirm the above statements.…”
Section: Discussionmentioning
confidence: 99%
“…PBO is also known to block nonspecific esterases in some insect species. [20][21][22] The involvement of nonspecific esterases in the cypermethrin resistance of T. tabaci must also be examined. 14) reported that most strains encoding T929I are arrhenotokous.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, esterase inhibition by OPs occurs 0.25-4 hr after in vivo application. 42) Gunning et al 69) and Moores et al 63) identified two ana-…”
Section: Heliothine Resistance To Spsmentioning
confidence: 99%
“…This is because H. armigera esterases are also inhibited by PBO. [59][60][61][62][63][64] However another study on a different species only saw this effect at high concentrations of PBO (3 mM) of dubious physiological relevance, whereas DEF at concentrations 100-fold lower shows a similar effect. 65) Other evidence that PBO does not have high affinity for the esterases is that the addition of PBO to extracts containing the H. armigera esterases prior to separation by native PAGE does not affect their esterase activity.…”
Section: Heliothine Resistance To Spsmentioning
confidence: 99%